Studi Penentuan Nilai Curve Number DAS Pataruman berdasarkan Satuan Peta Tanah Indonesia - Ramadan, Anri Noor Annisa; Nurmayadi, Dicky; Sadili, Anwar; Solihin, Rega Rizaldy; Sumardi, Zefri (Department of Civil Engineering, Diponegoro University, 2020)
The rainfall-runoff model is commonly used in flood discharge computation. One of the most frequently employed methods to estimate the flood discharge in the ungauged basin is NRCS-CN. This study is aimed to determine the CN value with/without soil drainage capacity from the soil information in SPT Indonesia. The location used is Pataruman watershed by calibrating the simulation discharge results with the observed discharge. Soil conditions in the Pataruman watershed show that the soil texture has a fine texture (HSG D), a slightly fine texture (HSG C), and a slightly coarse texture (HSG A). The average composite CN in the Pataruman watershed without soil drainage capacity was 85.58 while soil drainage capacity was 81.01. The results of the analysis show that with/without taking into account the soil drainage capacity in the Pataruman watershed there is no significant difference in discharge with a relation coefficient of 0.734 (without soil drainage capacity) and 0.732 (with soil drainage capacity). CN calculations with/without soil drainage capacity are recommended for small watersheds.